(untitled) (Journal of Partial Differential Equations, 1991)
We have obtained in this paper the existence of weak solutions to the Cauchy problem for a special system of quasillnear equations with physical interest of the form &#8706&#8706t(u + qz) + &#8706&#8706xf(u) = 0 &#8706z&#8706t + k&#966(u)z = 0 for the assumed smooth function &#966(u) by employing the viscosity method and the theory of compensated compactness.